La restauración de los colegios mayores en el siglo XX - Veci-Lavín, Carlos; MARTINEZ-NEIRA, MANUEL (Universidad Carlos III de Madrid. Figuerola Institute of Social Science History, 2025)
In the 20th century, Spain experienced an unprecedented collegiate movement that broke with the individualism of the Moyano law; in it, Krausist organicism and fin de siècle corporativism converged. The dictatorships of Miguel Primo de Rivera and Francisco Franco used the Colegio Mayor as the axis of university reform. The use of this category sought to legitimize a residential model at the service of a new ideology that had little to do with the experience of the Golden Age. The collegiate institution was called upon to move from a university that instructed to a university that educated, that formed a new Spanish citizen. The scope of the project can be perceived if we consider the more than one hundred colleges that were recognized or created between 1942 and 1959, as well as the purpose of boarding all university students. Along with the keys to the story, this volume offers a rich set of essential texts to understand the historical period addressed.